Black spot incidence and physic-chemical properties of guavas submitted to postharvest treatments - Fischer, Ivan Herman; Palharini, Maria Cecília de Arruda; Santos, Ana Paula dos; Nogueira Júnior, Antônio Fernandes; Parisi, Marise Cagnin Martins (Federal University of Piauí, 2016)
The guava fruit is very as high perishable due to its intense metabolism and the occurrence of postharvest diseases. Due to the lack conservation technologies for this fruit, this study aimed to evaluate the effect of alternative products [potassium phosphite, calcium chloride, cassava starch edible coat, 1-methylcyclopropene (1-MCP), ethanol followed by dichloro s. triazinatriona sodium (ethanol+chlorine)] and hot water treatments, singly or in combination, in black spot control and the physic-chemical characteristics of ‘Pedro Sato’ guavas. The treatments were evaluated in naturally infected guavas at three maturity stages and stored at 22-25ºC and 80-85% RH for 8 days. The treatment association of ethanol+chlorine and cassava starch reduced the incidence of black spot in three maturity stages of guavas, allowing the increase of fruit’s shelf life, with a delay of two to four days in the onset of black spot symptoms. The maintenance of the physical and chemical quality characteristics of guavas with association of treatments were evidenced by the delay in skin color change, and a smaller decrease in firmness. Correlation occurred between the black spot incidence and the skin color parameter, ie, fruits harvested at later maturity stages presented higher incidence of the disease. The greater efficiency of ethanol+chlorine/starch association in the control of black spot was directly related to the ripening delay in fruits, evidenced by the skin color and firmness attributes.